Flower size dimorphism, perianth shape and sex ratio in a gynodioecious Prunella vulgaris (Lamiaceae) - Godin Vladimir; Arkhipova Tatyana; Meier Natalia (BIO Web of Conferences, 2021)
Prunella vulgaris is a gynodioecious species that forms two types of flowers, perfect and female, on different plants. These two sexual types of flowers have significant differences in some characters of calyx, corolla, androecium, and gynoecium. The distinctiveness of gynodioecy in P. vulgaris consists in insignificant size differences in anthers, the formation of sterile pollen in female flowers, and the shape of a corolla in two sexual types of flowers. Hermaphrodite plants are dominated in P. vulgaris (59.8 to 87 percent). In flood plain meadows, the proportion of females is significantly higher (from 25.9 to 40.2 percent) than in dry and forest meadows (from 13 to 19.1 percent).